Creative Historical System and Modern Project of the “Qirq Qiz” Fortress - Khasanov Jurabek Kholboy ugli; Ismailov Mukhriddin Khusniddin ugli; Abdusalomov Jafar Abdukodir ugli (Zien Journals, 2022)
Preservation of our unique historical monuments, such as the architectural monument of the “Qirqqiz” Fortress is a sacred duty of every citizen living in the territory of Uzbekistan. After all, without historical and modern spirituality, without the development of enlightenment, it is impossible to build a state governed by the rule of law and civil society in our country. The article describes this.
Keywords: Kyrgyz; castle; architectural heritage; history